Construction of a high-potency anti-corrosive metal-organic film based on europium (III)-benzimidazole: Theoretical and electrochemical investigations. (1st February 2021) - Dehghani, Ali; Bahlakeh, Ghasem; Ramezanzadeh, Bahram; Hossein Jafari Mofidabadi, Amir
Graphical abstract: Highlights: EIS results proved 97% efficiency after 24 h for protected sample. BM:Eu complexes behaved as a mixed type inhibitor. Elemental analysis proved successful BM:Eu complexes adsorption. The theoretical investigations ascertained the binding of complexes on the steel. Abstract: A series of unique metal–organic films (MOFs) with excellent corrosion protection properties were constructed over the mild steel (MS) surface through covalent bonding between the benzimidazole (BM) molecules and europium (Eu) cations. The corrosion resistance of the MS samples protected by BM:Eu film was evaluated by electrochemical and morphological approaches in 3.5% NaCl solution. The interactions between BM and Eu were investigated by Fourier-transformed infrared (FT-IR) spectroscopy. Also, the π-π*/n-π* electro-transitions in the BM:Eu molecules in NaCl solution were proved by the UV–Vis technique. The FE-SEM images and GIXRD spectra showed the BM:Eu film deposition over the MS surface. Besides, in the presence of BM:Eu the amount of iron oxide drastically decreased. The Tafel curves demonstrated the mixed corrosion inhibition mechanism of the BM:Eu mixture on MS surface in saline solution. Electrochemical impedance spectroscopy (EIS) analysis results evidenced about corrosion inhibition efficiency of about 97% for the MS sample subjected to the 3.5% NaCl solution containing 200:600 ppm BM:Eu inhibitors. In addition, the theoretical insights including quantum mechanics (QM) and molecular dynamics (MD) computations, supported the adsorption of europium/benzimidazole molecules on the MS adsorbent.